ANALISIS PERSEPSI PEMAMFAATAN SISTEM INFORMASI KOMANDAN SIKD PADA PROVINSI DAN KABUPATEN/KOTA SULAWESI - Grace T. Pontoh; Mushar Mustafa (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2013)
Local Financial Information System National data Management and and communication (Komandan SIKD) is a web-based information system used by the local government to deliver data and information to the central goverment. Howewer, since its launching in december 2010, there are only a few local government using the 2011 KOMANDAN SIKD Information system. The Purpose of this research is to analyze factors which affect the KOMANDAN SIKD information system usage from the perspective of system user, The approach used in this research is quantitative with closed questionnaire method and placement of individuals as analysis unit . The result shows that TAM variabels have significant corelation with the intention pof using KOMANDAN SIKD, whereas the behavior control perception variabels is a TPB variable which does not share any significant corelation with the intention of using KOMANDAN SIKD . As such, the benefit of KOMANDAN SIKD information System are received by its users, in this case the local government, but the intention of using such system is curently hindered by the limited knowledge , capabilities and resources.